INTESTINAL FUNCTIONAL END-TO-END STAPLED ANASTOMOSIS WITH ENDOVASCULAR GASTROINTESTINAL ANASTOMOSIS STAPLERS IN SMALL DOGS AND CATS. - Genoni S (LIFE: International Journal of Health and Life-Sciences, 2024)
Intestinal functional end-to-end stapled anastomoses (FEESA) are reported to have lower complication rates than hand-sewn anastomoses in dogs, however, the size of standard gastrointestinal anastomosis (GIA) staplers prevents their use in small patients due to the reduced intestinal diameter. Our study investigates the use of endovascular gastrointestinal (endo-GIA) staplers to perform functional end-to-end intestinal anastomosis in small dogs (≤ 10 kg) and cats. Methods: Retrospective study approved by the Royal College of Veterinary Surgeons Ethics Review Panel (approval number 2022-144). The medical record databases of five referral hospitals were searched for patients that underwent an intestinal FEESA using an endo-GIA stapler. Dogs with a body weight ≤10 kg and cats were included. Patients were excluded if the available follow-up was less than ten days post-surgery, unless a major complication developed. Outcomes of interest for each patient included diagnosis, intraoperative complications, postoperative complications and survival time. Estimated survival was generated according to the Kaplan-Meier method. Differences between survival curves were tested by log-rank test. Results: Twenty-five patients (10 dogs and 15 cats) were enrolled in the study. The mean body weight was 5.18 kg (range 2.6 – 10 kg). Nine patients were diagnosed with neoplasia, 16 with non-neoplastic disease. The median follow-up was 126 days (range 18-896 days). No major complications were recorded. Five patients developed minor postoperative complications that included 3 superficial surgical site infections. Eighteen patients were alive at the end of the study, one was lost at follow-up. Of the 6 patients who died, none were dead because of complications from the intestinal surgery. Kaplan-Meier estimated survival was not reached. Survival was significantly longer for patients with non-neoplastic versus neoplastic disease (P = 0.005). Conclusions: Our study suggests that the use of endo-GIA stapling devices is safe and effective to perform functional end-to-end intestinal anastomosis in small patients